Power unpacked: domination, empowerment and participation in local Guatemalan peace forums - Idler, A; Mouly, C; Miranda, L (University of Bradford, Faculty of Social Sciences, 2015)
This article focuses on the various manifestations of power at play in a local peace initiative, the Guatemalan mesas de concertación – forums for consultation and follow-up of the peace agreements in English, or mesas in short. With this we hope to fill a void in the field of peace and conflict studies: the lack of a framework to systematically analyse the different dimensions of power in local peace initiatives. Drawing on qualitative data collected between 2002 and 2012, we use John Gaventa’s ‘power cube’ approach to explore spaces, forms and levels of power and how these interact.5 This includes how power shaped the establishment and evolution of the mesas, and how the mesas simultaneously sought to challenge unequal power structures, as well as to enable underrepresented social sectors to voice their concerns over peace implementation. We argue that the mesas were not only used by different stakeholders to contest and project power. They also reproduced structures of inequality and were prey to invisible power, which made it difficult for them to effectively enable marginalised social groups to achieve empowerment. Still, raising awareness about the significance that support across different levels of society has for the successful implementation of the Guatemalan peace agreements, the mesas promoted the participation and empowerment of a variety of social sectors, contributing to a more inclusive and locally grounded peace, and therefore a more sustainable one.